2001
DOI: 10.1063/1.1384013
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning and electrically forced jets. II. Applications

Abstract: Electrospinning is a process in which solid fibers are produced from a polymeric fluid stream ͑solution or melt͒ delivered through a millimeter-scale nozzle. This article uses the stability theory described in the previous article to develop a quantitative method for predicting when electrospinning occurs. First a method for calculating the shape and charge density of a steady jet as it thins from the nozzle is presented and is shown to capture quantitative features of the experiments. Then, this information i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
501
2
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(536 citation statements)
references
References 29 publications
19
501
2
14
Order By: Relevance
“…The increase of the current with Ca then becomes moderate; the current seems to level to a constant value, as in the experiments of Hohman et al (2001) and Riboux et al (2011), and even decreases slightly with increasing Ca (upper solid curves in figure la). At the same time, the radius of the jet increases and r s {x c )/a ceases to be small.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The increase of the current with Ca then becomes moderate; the current seems to level to a constant value, as in the experiments of Hohman et al (2001) and Riboux et al (2011), and even decreases slightly with increasing Ca (upper solid curves in figure la). At the same time, the radius of the jet increases and r s {x c )/a ceases to be small.…”
Section: Resultsmentioning
confidence: 85%
“…Hartman et al (1999) carried out experiments and numerical computations with ethylene glycol and nbutanol for various shapes of the injection nozzle and found that the exponent of the power law fitting their measured current for high flow rates is smaller than 1/2, and that the current depends on the shape of the electrode. Hohman et al (2001), in experiments with glycerol and polyethylene oxide (PEO)/water solutions in a parallel plate electrode configuration in which the injection tube protrudes from one of the plates, found that the electric current increases roughly linearly with the flow rate. The current also increases linearly with the voltage applied between the electrodes, except for very high voltages, for which the increase is faster than linear.…”
Section: Introductionmentioning
confidence: 99%
“…Hohman et al first presented a general theory for electrohydrodynamics applicable to the charged fluid jet that captured the competition between varicose and "whipping" instabilities. Significantly, for fluids of finite conductivity, a second varicose mode, dubbed the "conductive" mode, was identified [34][35][36]. The analysis of Hohman et al is valid for Newtonian fluids; the theory was subsequently extended to non-Newtonian fluids and nonisothermal conditions by several investigators [37][38][39].…”
Section: Electrospinningmentioning
confidence: 95%
“…In addition to this many material properties such as the intrinsic viscosity and bulk/surface charge density need to be determined experimentally before being incorporated into the models [32,[36][37][38][39][40][41]. Notwithstanding these difficulties, important models have been validated that describe different portions of the jet for selected materials.…”
Section: Introductionmentioning
confidence: 99%
“…Reneker et al created a mathematical model to explain the whipping instability based on the rheological properties of the polymer solution and lateral perturbations [32,36,41,44]. Hohman et al developed mathematical models for three different instabilities and used the models to create operating diagrams for when electrospinning occurs [37][38][39]. Feng created a 1D model based on slender body theory to examine the role of nonlinear rheology on the electrically stretched jet [40].…”
Section: Introductionmentioning
confidence: 99%